Penerapan Edupreneurship Berbasis Teaching Factory pada Unit Produksi Teknik Mesin di SMK Muhammadiyah Kramat - Sudiroh, Kiki Bagus; Afifah, Eka Nur; Nisa, Nurul Chaerun; Musthofa, Musthofa; Kuat, Tri (Indo-MathEdu Intellectuals Journal, 2026)
The implementation of Teaching Factory-based edupreneurship in Vocational High Schools (SMK) is an important strategy to prepare graduates who not only have technical competencies but also an entrepreneurial spirit. This study aims to describe the development of edupreneurship through the production unit of the Mechanical Engineering Department in the manufacture of step motors as an industry-based learning tool at SMK Muhammadiyah Kramat Tegal. The research uses a qualitative descriptive approach with data collection techniques in the form of observations of production unit activities, interviews with productive teachers and students, and documentation studies. The data were analysed using an interactive analysis model that included data reduction, data presentation, and conclusion drawing, with verification through source and technique triangulation. The results showed that the production unit functioned as contextual learning that integrated mechanical engineering competencies with entrepreneurial practices, ranging from production planning, manufacturing processes, quality control, to product marketing. This activity is able to improve students' technical skills, foster independence, responsibility, work discipline, and interest in entrepreneurship. Industry-based learning through production units provides learning experiences that are relevant to the needs of the world of work and industry.